Investigating the Relationship Between Perceived Romantic Relationship Quality in Parents and Psychological Resilience Levels of Adolescent During COVID-19 Pandemic Process - Akgül, Ömer; Akgül, Enise; Geçer, Ekmel; Söğütlü, Lütfiye; Tongar, Hatice Kübra; Körez, Muslu Kazım; Yıldırım, Murat (Erkan Mor, 2022)
Aim: Accumulated evidence shows that Coronavirus disease-2019 (COVID-19) pandemic related challenges have severely affected the mental well-being of many people around the globe including adolescents. This study examined the relationship between romantic relationship quality in parents and psychological resilience levels in adolescents during the COVID-19 pandemic. Materials and Methods: This cross-sectional online survey used self-reported measures of romantic relationship quality and resilience. Participants were 12.099 adults (99.2% female; mean age=35.27±5.37). Results: Results showed that romantic relationship quality was positively related to resilience. Those who reported increased marital satisfaction also reported higher levels of resilience, marital adjustment, and better relationship with adolescents. Conclusion: The study provided a new avenue for research that focuses on the link between romantic relationship quality, resilience and seeking emergency care within the context of the pandemic. Based on these results, prevention and intervention programs can be tailored and implemented to improve satisfaction in a romantic relationship.
Keywords: Covid-19; pandemi; iletişim; psikoloji; romantik; ilişki; yılmazlık; ergen